The Effectiveness of Mathematics Learning Through the Application of the Missouri Mathematics Project (MMP) Model in Grade 11 Students at Sman X - Ratni Dwita; Azzahra Nugrah; Yutia Nur Asmara; Karmelia Yuanda; Nabila Apri Yendri (Science Journal Get Press, 2025)
Effective mathematics learning demands a well-structured approach that encourages students to actively engage in comprehending mathematical concepts. This study explores the effectiveness of the Missouri Mathematics Project (MMP) learning model in improving the mathematics achievement of 11th-grade students at SMAN (X). A quantitative approach was used, employing a quasi-experimental design in the form of a one-group pretest-posttest design. The sample consisted of 30 students randomly selected from the 11th-grade population. Data collection involved two main instruments: an observation sheet to monitor the implementation of the MMP model, and a test of learning outcomes administered before and after the intervention. The results showed a notable improvement in student performance, with the average pretest score being 56.8 and the average posttest score rising to 81.2. Based on N-Gain analysis, a value of 0.65 was obtained, which is categorized as moderate, indicating a meaningful increase in learning outcomes. A paired sample t-test further confirmed this improvement, with a t-count of 8.32 and a significance level of p = 0.000 (p < 0.05). The implementation of the MMP model was rated highly, with an average score of 3.91 out of 4, falling into the excellent category. Moreover, 93.3% of the students achieved scores above the Minimum Completeness Criteria (KKM = 75), demonstrating individual mastery. These findings indicate that the MMP model is effective in enhancing mathematics learning outcomes. The model's structured nature supports active learning and can serve as a promising alternative teaching strategy in high school mathematics education.